Growth of children and adolescents with Down's syndrome. A brief review of the literature. DOI: 10.5007/1980-0037.2011v13n3p230 - José Irineu Gorla; Edison Duarte; Leonardo Trevisan Costa; Fábia Freire (Universidade Federal de Santa Catarina, 2011)
Physical growth is one of the most important aspects of child and adolescent growth. Measurements of weight and height using specific charts for each population are needed to adequately monitor growth. The aim of this study was to review the literature regarding growth curves for individuals with Down's syndrome (DS). Sources of the primary and secondary literature were reviewed searching the following databases: CREUSP, PubMed, Medline, and section libraries of UNICAMP. The results showed an approximate growth of -1.5 to -4 standard deviations in subjects with DS when compared to the general population, with this difference starting during the prenatal period and extending into adulthood. No major differences were found between studies conducted in different countries. In conclusion, patients with DS present growth retardation when compared to the general population, resulting in shorter final height.